Lipoteichoic acid of Streptococcus gordonii as a negative regulator of human dendritic cell activation - Kim, Sun Kyung; Im, Jintaek; Ko, Eun Byeol; Lee, Dongwook; Seo, Ho Seong; Yun, Cheol-Heui; Han, Seung Hyun (Frontiers in Immunology, 2023)
Streptococcus gordonii, an opportunistic Gram-positive bacterium, causes an infective endocarditis that could be fatal to human health. Dendritic cells (DCs) are known to be involved in disease progression and immune responses in S. gordonii infection. Since lipoteichoic acid (LTA) is a representative virulence factor of S. gordonii, we here investigated its role in human DCs activation stimulated with LTA-deficient (ΔltaS) S. gordonii and S. gordonii LTA. DCs treated with heat-killed ΔltaS S. gordonii (HKSG) showed relatively higher binding and phagocytic activities than those treated with wild-type HKSG. Furthermore, ΔltaS HKSG was superior to wild-type HKSG in inducing phenotypic maturation markers including CD80, CD83, CD86, PD-L1, and PD-L2, antigen presenting molecule MHC class II, and proinflammatory cytokines such as TNF-α and IL-6. Concomitantly, DCs treated with the ΔltaS HKSG induced better T cell activities, including proliferation and activation marker (CD25) expression, than those treated with the wild-type. LTA, but not lipoproteins, isolated from S. gordonii weakly activated TLR2 and barely affected the expression of phenotypic maturation markers or cytokines in DCs. Collectively, these results demonstrated that LTA is not a major immuno-stimulating agent of S. gordonii but rather it interferes with bacteria-induced DC maturation, suggesting its potential role in immune evasion.